The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.5582/bst.2023.01051
|View full text |Cite
|
Sign up to set email alerts
|

Optimized concurrent hearing and genetic screening in Beijing, China: A cross-sectional study

Abstract: Concurrent screening has been proven to provide a comprehensive approach for management of congenital deafness and prevention of ototoxicity. The SLC26A4 gene is associated with late-onset hearing loss and is of great clinical concern. For much earlier detection of newborns with deafnesscausing mutations in the SLC26A4 gene, the Beijing Municipal Government launched a chip for optimized genetic screening of 15 variants of 4 genes causing deafness based on a chip to screen for 9 variants of 4 genes, and 6 varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In 2012, Beijing launched a demonstration project of concurrent newborn hearing and deafness genetic screening. The project screened for nine mutations in four common deafness-related genes, such as c.235delC (p.Leu79Cysfs*3), c.299_300delAT (p.His100Argfs*14), c.176_191del16 (p.Gly59Alafs*18), and c.35delG (p.Gly12Valfs*2) in the GJB2 gene (MIM: 121011); c.919-2A > G and c.2168A > G (p.His723Arg) in the SLC26A4 gene (MIM:605646); m.1555A > G and m.1494C > T in mtDNA12SrRNA (MIM: 561000); and c.538C > T (p.Arg180*) in the GJB3 gene (MIM: 603324) ( 71 ). Currently, commonly used techniques for deafness genetic screening include microarray, PCR-fluorescent probe, fluorescent PCR, fluorescent PCR melting curve, PCR and flow-through hybridization, amplification refractory mutation system, PCR melting curve, combined probe anchoring polymerization sequencing, flight mass spectrometry sequencing, screening for known deafness-causing variants based on next-generation sequencing technology, and so on.…”
Section: The Present Stage Of Newborn Hearing Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Beijing launched a demonstration project of concurrent newborn hearing and deafness genetic screening. The project screened for nine mutations in four common deafness-related genes, such as c.235delC (p.Leu79Cysfs*3), c.299_300delAT (p.His100Argfs*14), c.176_191del16 (p.Gly59Alafs*18), and c.35delG (p.Gly12Valfs*2) in the GJB2 gene (MIM: 121011); c.919-2A > G and c.2168A > G (p.His723Arg) in the SLC26A4 gene (MIM:605646); m.1555A > G and m.1494C > T in mtDNA12SrRNA (MIM: 561000); and c.538C > T (p.Arg180*) in the GJB3 gene (MIM: 603324) ( 71 ). Currently, commonly used techniques for deafness genetic screening include microarray, PCR-fluorescent probe, fluorescent PCR, fluorescent PCR melting curve, PCR and flow-through hybridization, amplification refractory mutation system, PCR melting curve, combined probe anchoring polymerization sequencing, flight mass spectrometry sequencing, screening for known deafness-causing variants based on next-generation sequencing technology, and so on.…”
Section: The Present Stage Of Newborn Hearing Screeningmentioning
confidence: 99%
“…In 2022, a large cohort study of 3,555,336 newborns reported by Zhang et al ( 78 ) showed that GJB2 gene c.235delC was the most common variant in the Chinese newborn population, followed by SLC26A4 gene c.919-2A > G, differing from those in the Ashkenazi Jewish, European, and American populations. In 2023, the current authors’ research team ascertained the advantage of a screening chip including 15 variants of four genes and found that 71.43% of newborns with two variants of the SLC26A4 gene were screened for newly added mutations and 28.57% of newborns with two variants of the SLC26A4 gene passed the hearing screening, suggesting that a screening chip including 15 variants of four genes was superior at early detection of hearing loss, especially in early identification of newborns with deafness-causing mutations in the SLC26A4 gene ( 71 ). The genetic screening identified additional children who will possibly benefit from early intervention and informed at-risk newborns and their maternal relatives of increased susceptibility to ototoxicity ( 74 ).…”
Section: The Present Stage Of Newborn Hearing Screeningmentioning
confidence: 99%